Enhanced temporal resolution at cardiac CT with a novel CT image reconstruction algorithm: initial patient experience - Apfaltrer, Paul; Henzler, Thomas; Fink, Christian (European journal of radiology, 2013)
OBJECTIVE: To evaluate the effect of a temporal resolution improvement method (TRIM) for cardiac CT on diagnostic image quality for coronary artery assessment. MATERIALS AND METHODS: The TRIM-algorithm employs an iterative approach to reconstruct images from less than 180° of projections and uses a histogram constraint to prevent the occurrence of limited-angle artifacts. This algorithm was applied in 11 obese patients (7 men, 67.2 ± 9.8 years) who had undergone second generation dual-source cardiac CT with 120 kV, 175-426 mAs, and 500 ms gantry rotation. All data were reconstructed with a temporal resolution of 250 ms using traditional filtered-back projection (FBP) and of 200 ms using the TRIM-algorithm. Contrast attenuation and contrast-to-noise-ratio (CNR) were measured in the ascending aorta. The presence and severity of coronary motion artifacts was rated on a 4-point Likert scale. RESULTS: All scans were considered of diagnostic quality. Mean BMI was 36 ± 3.6 kg/m(2). Average heart rate was 60 ± 9 bpm. Mean effective dose was 13.5 ± 4.6 mSv. When comparing FBP- and TRIM reconstructed series, the attenuation within the ascending aorta (392 ± 70.7 vs. 396.8 ± 70.1 HU, p>0.05) and CNR (13.2 ± 3.2 vs. 11.7 ± 3.1, p>0.05) were not significantly different. A total of 110 coronary segments were evaluated. All studies were deemed diagnostic; however, there was a significant (p<0.05) difference in the severity score distribution of coronary motion artifacts between FBP (median=2.5) and TRIM (median=2.0) reconstructions. CONCLUSION: The algorithm evaluated here delivers diagnostic imaging quality of the coronary arteries despite 500 ms gantry rotation. Possible applications include improvement of cardiac imaging on slower gantry rotation systems or mitigation of the trade-off between temporal resolution and CNR in obese patients.